Repeat pulmonary vein isolation with or without FIRM‐guided ablation for recurrent atrial fibrillation with pulmonary vein reconnection. (9th March 2020) - Peigh, Graham; Wasserlauf, Jeremiah; Kaplan, Rachel M.; Amaral, Ansel P.; Trivedi, Amar; Chicos, Alexandru B.; Arora, Rishi; Kim, Susan; Lin, Albert; Verma, Nishant; Knight, Bradley P.; Passman, Rod S.
Abstract: Introduction: Focal impulse and rotor modulation (FIRM) ablation can be used to target nonpulmonary vein (PV) sources of atrial fibrillation (AF). No published studies have compared freedom from atrial fibrillation (FFAF) after pulmonary vein reisolation (PVRI) plus FIRM to PVRI alone in patients with reconnected PVs undergoing repeat ablation. Methods: A 3:1 matched retrospective cohort study was performed on 21 patients with recurrent AF and PV reconnection who underwent PVRI plus FIRM‐guided ablation and 63 patients with recurrent AF treated with PVRI alone at a single institution. All patients in the PVRI‐alone cohort had cryoballoon PVRI at the time of repeat ablation without additional lesion sets for AF. Cases were matched based on the type of AF (paroxysmal vs nonparoxysmal), left atrial diameter (±4 mm), left ventricular ejection fraction (±10%), duration of AF (±18 months), and age (±5 years). The primary endpoint was FFAF after a 3‐month blanking period. Results: Out of 53 total FIRM cases performed at Northwestern Memorial Hospital between 2015 and 2017, 21 patients had PVRI plus FIRM for recurrent AF with PV reconnection. These patients had an average of 3.3 ± 2.1 rotors (60% left atrial) ablated. Over a median follow‐up time of 24.7 months (interquartile range, 13‐36 months), patients in the PVRI‐alone cohort demonstrated a higher rate of FFAF (n = 35; 55.6%) than patients in the PVRI plus FIRM‐guided ablation cohort (n = 7; 33.3%) (logrank P  = .049). Conclusion: In patients undergoing repeat ablation for AF with PV reconnection, PVRI plus FIRM did not increase FFAF compared to PVRI alone.